Cut-off limits of the peak GH response to stimulation tests for the diagnosis of GH deficiency in children and adolescents: study in patients with organic GHD. Issue 1 (July 2016) - Guzzetti, Chiara; Ibba, Anastasia; Pilia, Sabrina; Beltrami, Nadia; Di Iorgi, Natascia; Rollo, Alessandra; Fratangeli, Nadia; Radetti, Giorgio; Zucchini, Stefano; Maghnie, Mohamad; Cappa, Marco; Loche, Sandro
Abstract : Objective: The diagnosis of GH deficiency (GHD) in children and adolescents is established when GH concentrations fail to reach an arbitrary cut-off level after at least two provocative tests. The objective of the study was to define the optimal GH cut-offs to provocative tests in children and adolescents. Design: Retrospective study in 372 subjects who underwent evaluation of GH secretion. GH and IGF-I were measured by chemiluminescence assay in all samples. Receiver operating characteristic (ROC) analysis was used to evaluate the optimal GH cut-offs and the diagnostic accuracy of provocative tests. Methods: Seventy four patients with organic GHD (GH peak <10μg/L after two provocative tests) and 298 control subjects (GH response >10μg/L to at least one test) were included in the study. The provocative tests used were arginine, insulin tolerance test (ITT) and clonidine. Diagnostic criteria based on cut-offs identified by ROC analysis (best pair of values for sensitivity and specificity) were evaluated for each test individually and for each test combined with IGF-I SDS. Results: The optimal GH cut-off for arginine resulted 6.5μg/L, 5.1μg/L for ITT and 6.8μg/L for clonidine. IGF-I SDS has low accuracy in diagnosing GHD (AUC=0.85). The combination of the results of provocative tests with IGF-I concentrations increased the specificity. Conclusions: The results of the ROC analysis showed that the cut-off limits which discriminate between normal and GHD are lower than those commonly employed. IGF-I is characterized by low diagnostic accuracy.